Perancangan Alat Pengukur Kecepatan dan Kekuatan Tendangan Serta Pukulan pada Beladiri dengan Sensor Force Sensing Resistor (FSR) Dan Nodemcu ESP32 - Ulfa Lunnisa; Haerul Pathoni; Yosi Riduas Hais (Universitas Batanghari Jambi, 2022)
This research aims to design a measuring device for the speed and strength of kicks and punches in martial arts so that the quality of kicks and punches can be measured objectively. The types of taekwondo kicks that were tested were ap chagi and yeop chagi as well as yeop jireugi and momtong jireugi punches. This research was conducted in several steps, namely: literature study, preparing tools and materials, designing and modeling, making tools and testing and analyzing data. The way this tool works, the respondent kicks or punches the foot boxing pad that has the FSR sensor installed. At the same time the time is started by pressing the start button. After making a kick or punch, the time will be stopped by pressing the stop button. The pressure and time will be read by the NodeMCU ESP32, the data will be sent via bluetooth to the Blynk application and displayed with the TM1637. The results of the research